Nursing safety management in onco-hematology pediatric wards - Marcelle Miranda da Silva; Bruna Irene Cunha Curty; Sabrina da Costa Machado Duarte; Karen Gisela Moraes Zepeda (Universidade Federal do Ceará, 2015)
This study aimed at identifying how safety management is applied by nurses to manage the nursing care, and at analyzing their challenges in onco-hematology pediatric wards. Descriptive and qualitative research, conducted at the Instituto Estadual de Hematologia Arthur de Siqueira Cavalcanti, Rio de Janeiro, Brazil, in August 2013. Six nurses were interviewed, and the content analysis was used. The key aspects relate to the importance of training and continuing education, teamwork, with the challenges in the care of hospitalized children and particularities of the disease, and the systematization, use of instruments and protocols. For child safety, the relationship between the administration and support is critical to the quality of care.